Effect of various materials used for semitransparent solar panel fitted at roof top of a building. (2022) - Gupta, Vidya Sagar; Gupta, Preeti; Tripathi, Rajesh; Sharma, Atul Kumar
Abstract: In this present work, the effect of various composition of materials used for manufacturing the solar panel and its effect on temperature of floor, room and solar cell has been computed along with the day light savings and electrical efficiency of solar cell. The present work on semi-transparent photovoltaic module built-in at the top of the roof of a building has been carried out in the winter season at Varanasi. The temperature coefficient and the electrical efficiency of the semi-transparent PV module influence the performance of the system. Different kind of silicon material (like Mono-Si, Poly-Si, amorphous Si) and PVT system have been studied and matched with state of art systems. It has been concluded that Photovoltaic Thermal system has been suggested for energy gain and Mono-silicon material for electrical exergy due to decrease in overall exergy efficiency by 4.39%.